Enhancing tomato growth and soil fertility under salinity stress using halotolerant plant growth-promoting rhizobacteria - Ning Yan; Weichi Wang; Tong Mi; Xuefeng Zhang; Xinyue Li; Guodong Du (Plant Stress)
Soil salinization is a critical issue that not only hampers the efficiency and sustainability of global agricultural production but also poses significant challenges to the achievement of sustainable development goals across environmental, economic, and social dimensions. Halotolerant plant growth-promoting rhizobacteria (HPGPR) have the potential to mitigate abiotic stress, foster plant growth, and bolster the stress resistance capabilities of crops. This study conducted the isolation, identification, and characterization of HPGPR originating from a saline-alkali orchard area in northwest China. The efficacy of the isolated bacterial strains was evaluated through potted plant experiments, assessing the growth of tomato plants under in vitro conditions and under varying salinity stress. Ultimately, the study investigated the influence of these HPGPR on soil physicochemical properties, enzymatic activities, and the structure and composition of the microbial community. Upon isolating 12 bacterial strains, we conducted an in vitro assessment of their salt tolerance, ultimately singling out three robust isolates, which exhibited exceptional salt tolerance. Detailed 16S rRNA gene sequencing and meticulous taxonomic evaluation systematically assigned these isolates to Priestia endophyticus GSCK1 (accession number: OR569048), Bacillus atrophaeus GSCK2 (accession number: OR569061), and Serratia fonticola GSCK6 (accession number: OR569062), respectively. These strains exhibited notable biochemical and plant growth-promoting traits, including enzymatic activities and the production of indole-3-acetic acid. They significantly enhanced plant growth metrics and soil fertilities, particularly strain GSCK6, which also reshaped the soil microbial community, augmenting beneficial microbe abundance. The HPGPR treatment notably improved soil pH, nutrient availability, enzymatic activities, and reduced soil electrical conductivity, underscoring their potential in agricultural resilience against salinity. The eco-friendly salt stress mitigation strategy of HPGPR not only enhances soil quality and promotes plant growth by regulating the composition and function of microbial communities, but also provides a novel solution for global agricultural production. This approach is conducive to increasing crop yield and quality, reducing the limitations of saline-alkali land on agricultural production, and promoting food security and sustainable agricultural development.